Intensified butanol production through optimisation of integrated membrane bioreactor operation - Lipnizki, Frank ; 0000-0002-3008-0182; Outram, Victoria ; 0000-0002-0216-6114 (European Congress on Biotechnology 2024, Rotterdam, Netherlands, 2024-06-30 - 2024-07-03, 2024)
Fermentation intensification is crucial for the economic viability of biobased chemical production through fermentative routes, including a shift from batch/fed-batch to continuous fermentations to enhance volumetric productivity. This is especially relevant for the Acetone Butanol Ethanol (ABE) fermentation due to low productivities and concentrations caused by product toxicity. However, transitioning to a stable continuous process faces challenges, often resulting in oscillatory fermentations and low product titres due to the complex ABE pathway and byproduct interactions. To address this, we integrated a membrane into the fermenter for continuous product removal, reducing inhibition while increasing the biomass residence time. Without the membrane, cell density reached 0.6 g/L and a butanol productivity 0.10 g/L·h. With the membrane, cell density tripled to 1.8 g/L, though maintaining this proved challenging as the permeate flux decreased after 50 hours, resulting in cell loss. Sustaining a flux of 20 kg/m²·h was critical for fermentation performance. Initial backflushing (10 seconds every 2 minutes) maintained a flux at 19 kg/m²·h but diluted the broth significantly to 0.7 gBiomass/L. Optimizing backflushing allowed for a reduction in the frequency to every 20 minutes, resulting in an 85% reduction in the dilution factor, leading to a peak cell density of 3 g/L and an average of 2 g/L (three times higher than the control without a membrane). Butanol productivity increased by 24% to 0.13 g/L·h, sustaining stable operation for 150 hours. This study demonstrated successful operation of a membrane bioreactor for 150 hours. Further optimization can enhance productivity, boosting sustainable manufacturing viability.
Keywords: Fermentation; Membrane bioreactors